Assessing Inclusivity vs. Exclusivity: Impacts on ASEAN Trade Facilitation and Human Security - Putranti, Ika Riswanti; Warsono, Hardi; Paganizza, Valeria; Hadi, Dedi Abdul; Alfian, Muhammad Faizal; Subhan, Muhammad; Fatharini, Anjani Tri; Hudaya, Maula; Zuliyan, Muhammad Arief; Setiyaningsih, Dewi (UI Scholars Hub, 2024)
The ATIGA (Association of Southeast Asian Nations Trade in Goods Agreement) is an evolution of economic cooperation among ASEAN member countries which began in 1977 with the PTA (Preferential Trade Agreement) embryonic concept and was developed in the 1990s with the CEPT (Common Effective Preferential Tariff). It has driven a significant increase in intra-trade and external trade in the Southeast Asian region. The agreement was to establish a free trade zone that provides the concept of “preferences” by reducing tariff and non-tariff barriers for member countries in order to encourage regional economic growth through trade creation and trade diversion is considered capable of strengthening the integration of regional regionalism. Indonesia is one of the key players in ASEAN and is interested in being able to increase its role in trade and economic development in the Southeast Asian region. It continues to strive to ensure commitment to implement the ATIGA can be realized by opening the widest possible access for all elements. Indonesians can take advantage of the facilities provided in international agreements. This research uses a qualitative explanatory method. The research finding shows in line with the increase in the flow of goods and services in the region, the challenges of implementing a regional free trade zone are also increasingly complex and causing several impacts that need to be studied immediately, such as environmental issues, food security, terrorism, intellectual property rights, and human rights. The paradox of service versus security in service-oriented trade facilities should not simply abandon the element of oversight to safeguard national interests, one of which is in the aspect of fulfilling human security.